2011
DOI: 10.1177/0269881111408461
|View full text |Cite
|
Sign up to set email alerts
|

Second generation antipsychotics in the treatment of bipolar depression: a systematic review and meta-analysis

Abstract: Please list at least 3 keywords which relate to your manuscript::second generation antipsychotics, depressive episode, bipolar disorder, placebo, meta-analysis Abstract:Depressive symptoms and episodes dominate the course of bipolar disorder. However, the therapeutic armamentarium for bipolar depression is limited. Recent evidence points at the efficacy of second generation antipsychotics (SGAs) for the treatment of bipolar depression. We conducted a systematic review and meta-analysis of the efficacy and safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 47 publications
1
39
1
2
Order By: Relevance
“…In these studies, efficacy was evaluated using the MADRS and the CGI-BP, as was done in this study. In addition, a meta-analysis demonstrated the efficacy of olanzapine for improving the MADRS total score [12]. The pharmacological mechanism of action of olanzapine for treating depression is thought to be based on an increase in dopamine and noradrenaline release in the prefrontal cortex [13] and on 5-HT2A and 5-HT2C receptor antagonistic activity [14].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, efficacy was evaluated using the MADRS and the CGI-BP, as was done in this study. In addition, a meta-analysis demonstrated the efficacy of olanzapine for improving the MADRS total score [12]. The pharmacological mechanism of action of olanzapine for treating depression is thought to be based on an increase in dopamine and noradrenaline release in the prefrontal cortex [13] and on 5-HT2A and 5-HT2C receptor antagonistic activity [14].…”
Section: Discussionmentioning
confidence: 99%
“…38 Atypical antipsychotics have been investigated in bipolar depression with variable results. 39 Treatment with quetiapine leads to more symptomatic improvement in patients with bipolar depression than do placebo, paroxetine, and lithium. 39 Some evidence exists of a reduced risk of recurrence in patients who respond to acute-phase treatment and continue quetiapine rather than switch to placebo; thus, continuation could be of benefit in patients who can tolerate the drug's adverse effects, including sedation and weight gain.…”
Section: Treatment Of Bipolar Depressionmentioning
confidence: 99%
“…Emerging evidence suggests that lurasidone might also be efficacious, whereas aripiprazole does not seem to be so. 39,42 The transdiagnostic benefits of a drug like quetiapine, which is antipsychotic, antimanic, and antidepressant in both unipolar and bipolar depression, emphasises the importance of the investigation of treatment effects across conventional diagnostic boundaries. 9,40,43 However, this nonspecificity and scarcity of convincing evidence of long-term disease modification by known mechanisms suggests that the effects are mediated by short-term alleviation of symptoms.…”
Section: Treatment Of Bipolar Depressionmentioning
confidence: 99%
“…The natural compounds containing the quinolin-2-one nucleus such as flindersine, dictamnine as well as their synthetic analogues are found to possess pharmacological activity and therapeutic utility [2][3][4][5]. Clinical significance of quinolin-2-one is well established and documented in the form of treatment of psychosis, as a β-blocker in an ophthalmic preparation, as an antacid and in congestive cardiac failure [6][7][8][9]. Literature reviews have indicated linomide ( fig.…”
Section: Introductionmentioning
confidence: 99%